2006
DOI: 10.1007/s10573-006-0060-4
|View full text |Cite
|
Sign up to set email alerts
|

Detonation of propane-air mixtures under injection of hot detonation products

Abstract: The tube for spontaneous detonation (Institute of Technical Physics, Russian Federal Nuclear Center, Snezhinsk) was used to study the initiation and development of detonation in propane-air mixtures under injection of hot detonation products into them. The full picture of this phenomenon was recorded: the injection of hot detonation products into the main tube of the facility with the formation of a mixture of the starting propane-air composition with the hot products; the initiation of a local explosion in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Despite the fact that the FeAl phase is stable up to 1310 °C ( Figure 4 ), the first temperature range was selected to be from 0 °C to 1395 °C, which is the model liquidus temperature for the Fe40Al at.% alloy. The second range from 1395 °C to the conventional evaporation temperature of 2690 °C was determined on the basis of the arithmetic mean of the evaporation temperatures of Al and Fe [ 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Technological Conditions In Dgs Processmentioning
confidence: 99%
“…Despite the fact that the FeAl phase is stable up to 1310 °C ( Figure 4 ), the first temperature range was selected to be from 0 °C to 1395 °C, which is the model liquidus temperature for the Fe40Al at.% alloy. The second range from 1395 °C to the conventional evaporation temperature of 2690 °C was determined on the basis of the arithmetic mean of the evaporation temperatures of Al and Fe [ 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Technological Conditions In Dgs Processmentioning
confidence: 99%
“…Tarzhanov et al [13] investigated using hot detonation products to detonate stagnant propane-air mixtures. They found that detonation initiation depends on the initial volume concentrations of the mixture, mass fraction of hot detonation products, and the energy deposited from the detonation products.…”
Section: Introductionmentioning
confidence: 99%
“…Chemically reactive radicals (e.g., H and OH) and jet-induced turbulence are estimated as equivalent to two orders of magnitude higher energy than spark ignition [2]. Tarzhanov et al [13] investigated using hot detonation products to detonate stagnant propane-air mixtures and found that detonation initiation depends on the initial volume concentrations, mass fraction of hot detonation products, and the energy deposited from the detonation products. Mayinger et al [14] derived correlations between the induction time (ignition delay time), the mixing time of the jet, and the adiabatic autoignition time for the fuel-air mixtures.…”
Section: Introductionmentioning
confidence: 99%